Quality of life after postmastectomy radiotherapy in patients with intermediate-risk breast cancer (SUPREMO): 2-year follow-up results of a randomised controlled trial. Issue 11 (November 2018) - Velikova, Galina; Williams, Linda Jane; Willis, Sarah; Dixon, J Michael; Loncaster, Juliette; Hatton, Matthew; Clarke, Jacqueline; Kunkler, Ian H; Russell, Nicola S; ,
Summary: Background: Postmastectomy radiotherapy in patients with four or more positive axillary nodes reduces breast cancer mortality, but its role in patients with one to three involved nodes is controversial. We assessed the effects of postmastectomy radiotherapy on quality of life (QOL) in women with intermediate-risk breast cancer. Methods: SUPREMO is an open-label, international, parallel-group, randomised, controlled trial. Women aged 18 years or older with intermediate-risk breast cancer (defined as pT1–2N1; pT3N0; or pT2N0 if also grade III or with lymphovascular invasion) who had undergone mastectomy and, if node positive, axillary surgery, were randomly assigned (1:1) to receive chest wall radiotherapy (50 Gy in 25 fractions or a radiobiologically equivalent dose of 45 Gy in 20 fractions or 40 Gy in 15 fractions) or no radiotherapy. Randomisation was done with permuted blocks of varying block length, and stratified by centre, without masking of patients or investigators. The primary endpoint is 10-year overall survival. Here, we present 2-year results of QOL (a prespecified secondary endpoint). The QOL substudy, open to all UK patients, consists of questionnaires (European Organisation for Research and Treatment of Cancer QLQ-C30 and QLQ-BR23, Body Image Scale, Hospital Anxiety and Depression Scale [HADS], and EQ-5D-3L) completed before randomisation, and at 1, 2, 5, and 10 years. The prespecified primary outcomes within this QOL substudy were global QOL, fatigue, physical function, chest wall symptoms, shoulder and arm symptoms, body image, and anxiety and depression. Data were analysed by intention to treat, using repeated mixed-effects methods. This trial is registered with the ISRCTN registry, number ISRCTN61145589. Findings: Between Aug 4, 2006, and April 29, 2013, 1688 patients were enrolled internationally and randomly assigned to receive chest wall radiotherapy (n=853) or not (n=835). 989 (79%) of 1258 patients from 111 UK centres consented to participate in the QOL substudy (487 in the radiotherapy group and 502 in the no radiotherapy group), of whom 947 (96%) returned the baseline questionnaires and were included in the analysis (radiotherapy, n=471; no radiotherapy, n=476). At up to 2 years, chest wall symptoms were worse in the radiotherapy group than in the no radiotherapy group (mean score 14·1 [SD 15·8] in the radiotherapy group vs 11·6 [14·6] in the no radiotherapy group; effect estimate 2·17, 95% CI 0·40–3·94; p=0·016); however, there was an improvement in both groups between years 1 and 2 (visit effect −1·34, 95% CI −2·36 to −0·31; p=0·010). No differences were seen between treatment groups in arm and shoulder symptoms, body image, fatigue, overall QOL, physical function, or anxiety or depression scores. Interpretation: Postmastectomy radiotherapy led to more local (chest wall) symptoms up to 2 years postrandomisation compared with no radiotherapy, but the difference between groups was small. These data will inform shared decision making while we await survival (trial primary endpoint) results. Funding: Medical Research Council, European Organisation for Research and Treatment of Cancer, Cancer Australia, Dutch Cancer Society, Trustees of Hong Kong and Shanghai Banking Corporation.